Introduction: Remembering Gianni Vattimo - Snyder, Jon R. (California Italian studies, 2024)
In the course of its existence, California Italian Studies has published essays by living Italian philosophers who were luminaries in the field, including Umberto Eco and Franco Cassano (now both deceased). Somehow, however, the pages of this journal never until now have hosted any contribution by Gianni Vattimo, the great Italian philosopher who passed away in September 2023 at age 87. Vattimo was a beloved teacher, a mentor, and a friend to several of the founding members of CIS , myself included, so it seems particularly appropriate for us to offer a posthumous homage to him in this open-theme issue of volume 13. I will offer just a few personal reminiscences here, as both Maurizio Ferraris and Simonetta Moro address in their respective essays the core tenets of Vattimo’s philosophy. Vattimo’s brief 1985 essay on myth and truth is included here because it so succinctly summarizes and illustrates the strand of his work for which he is most remembered today, namely il pensiero debole or “weak thought.”